Optimal Approximate Solution of the Matrix Equation $AXB=C$ over Symmetric Matrices (Journal of Computational Mathematics, 2007)
Let $S_E$ denote the least-squares symmetric solution set of the matrix equation $AXB=C$, where $A$, $B$ and $C$ are given matrices of suitable size. To find the optimal approximate solution in the set $S_E$ to a given matrix, we give a new feasible method based on the projection theorem, the generalized SVD and the canonical correction decomposition.